PERBEDAAN SIKLUS MENSTRUASI ANTARA IBU YANG MENGGUNAKAN AKDR DAN ALAT KONTRASEPSI SUNTIK DI DESA BERUK KABUPATEN KARANGANYAR - Warsini -; Ipung Wulandari; Tri Handayani (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
AbstractIntroduction: An increase in the rate of population growth in Indonesia is increasingly rapidly. One way to control the rate of population growth is by family planning program (KB). Growing family planning programs are administered by the Government, is also increasingly developing contraceptives, such as pills, IUD, implants, sterilizing men, seterilisasi women, condoms, periodic abstinence and copulation is disconnected. In addition to the function to control the population, AKDR and contraceptive injection had side effects, the most important is related to disorders of menstruation. From the results of a survey in Desa Beruk retrieved data. There are 154 KK which resides and 52 KK are acceptors KB which includes AKDR and contraceptive injection and some of them also complained of experiencing menstrual disorders.The Purpose: To tell the difference between the mother's menstrual cycle which uses AKDR and contraceptive injection in Desa Beruk Kabupaten Karanganyar.Methods: This study is a comparative analytical research by design with cross sectional design.Subjects: Acceptors KB type AKDR and syringe in Desa Beruk Kabupaten Karanganyar amounted to 52 people. The sample in this study is taken based on table Krecjie so obtained the result total sample of 44 people. Sampling simple random way (simple random sampling).Results: Menstrual cycle most often in AKDR is normal usage with a range between 12 and 28 days, whereas in the use of contraceptive injection cycles most often happens is polimenore with the average cycle is 19 days with a range of 14 to 30 days. Mann Whitney test results was p = 0,032.Conclusion: Because the value of p can be inferred then 0.05 < that there are meaningful differences between the menstrual cycle on the use of AKDR and menstrual cycle use of contraceptive injection.Keywords: the difference, menstrual cycle, contraceptive injection, AKDR